Prognostic Factors for COVID-19 Pneumonia Progression to Severe Symptoms Based on Earlier Clinical Features: A Retrospective Analysis - Huang, Huang; Cai, Shuijiang; Li, Yueping; Li, Youxia; Fan, Yinqiang; Li, Linghua; Lei, Chunliang; Tang, Xiaoping; Hu, Fengyu; Li, Feng; Deng, Xilong (Frontiers in Medicine, 2020)
Approximately 15-20% of COVID-19 patients will develop severe pneumonia, about 10 % of which will die if not properly managed. Earlier discrimination of the potential severe patients basing on routine clinical and laboratory changes and commencement of prophylactical management will not only save their lives but also mitigate the otherwise overwhelmed health care burden. In this retrospective investigation, the clinical and laboratory features were collected from 125 COVID-19 patients, who were classified into mild (93 cases) or severe (32 cases) groups according to their clinical outcomes after 3 to 7-days post-admission. The subsequent analysis with single-factor and multivariate logistic regression methods indicated that 17 factors on admission differed significantly between mild and severe groups, but that only comorbid with underlying diseases, increased respiratory rate (>24/min), elevated C-reactive protein (CRP >10mg/liter), and lactate dehydrogenase (LDH >250U/liter), were independently associated with the later disease development. Finally, we evaluated their prognostic values with the receiver operating characteristic curve (ROC) analysis and found that the above four factors could not confidently predict the occurrence of severe pneumonia individually, but that a combination of fast respiratory rate and elevated LDH significantly increased the predictive confidence (AUC= 0.944, sensitivity= 0.941, and specificity= 0.902). A combination consisting of 3- or 4-factors could further increase the prognostic value. Additionally, measurable serum viral RNA post-admission independently predicted the severe illness occurrence. In conclusion, a combination of general clinical characteristics and laboratory tests could provide high confident prognostic value for identifying potential severe COVID-19 pneumonia patients.